2009
DOI: 10.1074/jbc.m806902200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidizable Residues Mediating Protein Stability and Cytoprotective Interaction of DJ-1 with Apoptosis Signal-regulating Kinase 1

Abstract: 2 (1). The most dramatic PD-associated mutation L166P impairs DJ-1 dimer formation and dramatically destabilizes the protein (2-7). Other mutations such as M26I (8) and E64D (9) have more subtle defects with unclear cellular consequences (4, 7, 10, 11). In addition to this genetic association, DJ-1 is neuropathologically linked to PD. DJ-1 is up-regulated in reactive astrocytes, and it is oxidatively modified in brains of sporadic PD patients (12)(13)(14).DJ-1 protects against oxidative stress and mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
184
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(192 citation statements)
references
References 50 publications
8
184
0
Order By: Relevance
“…Mutant proteins DJ-1(C53A) and DJ-1(C106A) were cloned and purified. The single mutation of Cys-46 (C46A) produces an unstable protein, which is prone to degradation (25,34), and the C46S, which we cloned and purified, is more unstable than the other single mutant proteins. Therefore, to obtain information on Cys-46 indirectly, a double mutant, DJ-1(C53A/C106A), was prepared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant proteins DJ-1(C53A) and DJ-1(C106A) were cloned and purified. The single mutation of Cys-46 (C46A) produces an unstable protein, which is prone to degradation (25,34), and the C46S, which we cloned and purified, is more unstable than the other single mutant proteins. Therefore, to obtain information on Cys-46 indirectly, a double mutant, DJ-1(C53A/C106A), was prepared.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the full cytoprotective activity of DJ-1 seems to require a more complete, mixed disulfide-mediated incorporation into the ASK1 signalosome, for which Cys-106 is necessary. It has been suggested that the C106DD mutation only "opens" the conformation of DJ-1 to reveal ASK1 binding site(s), resulting in the observed ASK1 binding and partial cytoprotection (34). Also this functional hypothesis requires Cys-106, which would be severely compromised by DAQ binding.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, this interaction was enhanced in NT after LPS challenge in a time-dependent manner ( Figure 7A). As Cys106 oxidation is important for Park7 interaction with other proteins [37], we then examined whether Park7 was oxidized in our experimental system. NT cells showed significantly increased Park7 oxidation after PMA treatment (Supplementary information, Figure S8), suggesting that the enhanced Park7-p47 phox interaction may be attributed to the increased Park7 oxidation level.…”
Section: Ros Modulate Lps-induced Proinflammatory Cytokine Productionmentioning
confidence: 99%
“…Considering the high propensity of Cys-106 to oxidize, it has been proposed that DJ-1 acts merely as a direct ROS scavenger. However, an elegant new study reported that the DJ-1 C106DD mutant is still able to protect cells against oxidative stress (70), excluding direct scavenger action by Cys oxidation.…”
mentioning
confidence: 99%